SBOX- A Smart Medicine Box / Anis Raihana Abdullah - Abdullah, Anis Raihana (2020)
Nowadays, various type of products were invented involving high technology that could make consumer’s life more easily or perhaps faster than usual. However, they still fail to produce a product that give advantages for people who need to consume regular medicine daily, which is one of the reason The SBOX is invented by our company. The SBOX, a smart technology box that is need to be introduced to the market. This product target form mass consumer, elders who keep on forgetting to consume daily medicine, adults or workers who are busy to manage their own time and leading to not consume the right amount of medicine, teenagers and even children with their parents guidance. The SBOX, a product that is easy to set up and use even for consumers who does not experts to use technologies. This set of product also come with a guidance that is easily to understand from all type of consumers. It is a very useful product that can easily turn on and off whichever the consumers want it to be. A clear and loud sound of the alarm installed in this product make it impossible to ignore and forgotten. Also, this product is convenience for people as it is chargeable, small and light weight make it easier to bring anywhere. Here, our company highlight on high technologies equipment which is totally safe from any complication that can make the medicine rotten or unsafe. With this product, our time to consume medicine either once or twice a day are neatly organized.